Nigrostriatal Dopaminergic Dysfunction and Altered Functional Connectivity in REM Sleep Behavior Disorder With Mild Motor Impairment - Yamada, Gohei (Front Neurol, 2019)
Rapid eye movement sleep behavior disorder is parasomnia characterized by symptoms of dream enactment and loss of muscle atonia during rapid eye movement sleep. Mild motor impairment is present in some patients with rapid eye movement sleep behavior disorder and presumed to be a risk factor for conversion to synucleinopathies. The purpose of this study is to identify patients with mild motor impairment by evaluating finger tapping and to investigate its pathophysiology. Twenty-three patients with rapid eye movement sleep behavior disorder and 20 healthy control subjects were recruited in the present study. We accurately evaluated finger tapping including amplitude, peak open, and close speed with a magnetic sensing device and identified patients with mild motor impairment. Moreover, we performed (123)I-2β-carbomethoxy-3β-(4-iodophenyl) nortropane SPECT and resting state functional MRI. (123)I-2β-carbomethoxy-3β-(4-iodophenyl) nortropane uptake for each bilateral caudate, anterior putamen, and posterior putamen was calculated and the resting state functional connectivity of sensorimotor network was analyzed. Using finger tapping parameters, we identified eight patients with mild motor impairment. In patients with mild motor impairment, all finger tapping parameters were significantly impaired when compared to patients with normal motor function, while they exhibited no significant differences in Unified Parkinson's Disease Rating Scale part III score. (123)I-2β-carbomethoxy-3β-(4-iodophenyl) nortropane uptake in the right posterior putamen, bilateral anterior putamen, and caudate was significantly lower when compared to healthy controls or patients with rapid eye movement sleep behavior disorder with normal motor function. These patients also exhibited decreased cortico-striatal functional connectivity and increased cortico-cerebellar functional connectivity when compared to healthy controls or patients with normal motor function. Our results show that mild motor impairment in rapid eye movement sleep behavior disorder evaluated by finger tapping task presented mild nigrostriatal dopaminergic dysfunction as well as alterations in resting state sensorimotor network. Although longitudinal follow up is necessary, such patients may have higher risk of short-term conversion to synucleinopathies.